The Role of Corruption and Healthcare Expenditure in Healthcare Systems of the Persian Gulf Region - Maryam Asghari (علوم بهداشتی ایران, 2016)
Background and Purpose: More than a third of the world’s population lack access to essential medicines, despite the presence of several international agreements that proclaim health as a human right. Corruption, in its many forms, such as bribery and embezzlement, causes several detrimental effects on the health sector and access to medicines including economic, health, and government image and trust issues. Global health corruption remains a serious, ongoing, and under-recognized threat to global health progress. This paper aim is examination how global corruption and health-care expenditure (HE) affect health statue in the Persian Gulf countries over 1980-2014 and what can be done to combat corruption in the health sector.